Syntaktyka a metody eksperckie kategorie składniowe wyrazów odmiennych koniugacyjnie - Olejnik, Roman Marcin (Syntactics and the expert methods - syntactic categories of conjugatively different words, 2005)
The purpose of the general considerations included in the paper „Syntactics and the experts methods”, is the examination of the logic (syntactic) dimension of information carriers, including the statements being a particular case of semantic networks. Semantic networks represent relationships between domain elements (network nodes) by defining relation connections between nodes, or so called arcs. In linguistic categories, the arcs are functors, or lingual expressions being neither designation nor statement, but serving for the creation of compound expressions. The subject of detailed considerations will be the syntactic analysis of those types of functors, which, in grammar, correspond to the part of speech subject to conjugative inflection, that is verbs. A creative and methodological element of the study will be an attempt to name all possible syntactic codes of these functors, relating to specific contexts. A methodological novelty of these considerations is the introduction and an attempt of using the notion vertical multiplication. It serves, as an operational activity, for defining the syntactic category of different types of functors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 123-138